Interplay Between Intestinal pH, Transit Time and Feed Status on the In Vivo Performance of pH Responsive Ileo-Colonic Release Systems - Ibekwe, Valentine C.; Fadda, Hala M.; McConnell, Emma L.; Khela, Mandeep K.; Evans, David F.; Basit, Abdul W. (Pharmaceutical research, 2008)
Purpose Oral pH triggered drug delivery systems, for targeting to the lower gastrointestinal tract, show erratic behaviour in vivo . This study aimed to establish correlations between in situ gastrointestinal pH, transit time or feed status and the disintegration of pH-responsive dosage forms designed to dissolve above pH 7. Methods Tablets (radiolabelled with Technetium 99m) coated with Eudragit S were administered to eight healthy subjects in a three-way crossover study after an overnight fast. Food was administered either 30 min after (pre-feed) or 4 h after (fasted) tablet ingestion. Concurrently, a Bravo® pH monitoring capsule (radiolabelled with Indium 111) was administered in a “freefall manner”. In a third arm of the study tablets were given immediately after breakfast (fed). Transit was followed by gamma scintigraphy. Results Gastrointestinal pH showed variability between and within individuals but no differences were seen between pre-feed and fasted states. Three tablets failed to disintegrate in pre-feed and fed regimens and one in the fasted state; this has been tentatively linked to ileocaecal pH and ileoceacal junction residence time. Conclusions In vivo performance of “pH-responsive” dosage forms is complex and influenced by a multitude of factors other than just in situ pH.